The international practices of services rendered to population by public and local authorities - A. B. Lys (Aspekti Publìčnogo Upravlìnnâ, 2015)
The article deals with the analysis of the peculiar providing of administrative services to citizens within the context of ‘service’ state functioning. The ‘service’ state is viewed as the one that reflects the requirements, needs, and aspirations of the modern postindustrial, democratic and liberal society to the highest extent. Analyzing this particular experience of the developed countries in Europe and the world, the author singles out the key ways of its integration into the public and local authorities of Ukraine. The author has overviewed the international experience of regulation and control of processes and procedures of quality services at public authorities in the US, Belgium, Portugal, France, Germany, Poland, Estonia, Latvia, Hungary. The processes and results of interaction of pairs of typical administrative relations between the subjects of the process of administrative services «an appeal» have not yet observed. The experience of other countries clearly demonstrates that all state and business bureaucracy in its management activities is and will be efficient and effective only under the condition where the activity will build on the foundation of conceptual latest knowledge about man, society and the state, the principles and laws of their development, about modern organizational innovation, innovation management technologies, organizational mechanisms and tools, capabilities and potential use in the processes of government and public service of modern information and computer technologies. The next challenges, facing Ukraine authorities to ensure the quality of dministrative services, have been determined in the article: rethinking of public servants and employees of government of its functions based on the requirements, needs and aspirations of a newly liberalized and democratized society; the requirements of the formation of the staff of the competent administrative workers with post-industrial ideological and value system; significant increase ethical and intellectual potential of all staffing.